IMMUNOPATHOLOGICAL CHANGES IN SHEEP EXPERIMENTLY INFCETED WITH MYCOPLASMA OVIPNEUMONIAE BY INTRANASAL AND INTRATRACHEAL ROUTES - Zainab W. Khutair; Z. I. Ibrahim; F. A. Abdallah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Mycoplasma ovipneumoniae (M. ovipneumoniae) is a type of contagious bacteria have respiratory clinical signs; nasal mucinous discharge, sneezing, coughing, dullness, and in some cases with diarrhea and the necropsy findings represent lesions of pneumonia in different stages; pulmonary edema and hyperemia, consolidation, hemorrhage and hepatization.  that causes atypical pneumonia and pleuropneumonia in small ruminants, it is belongs to a group of bacteria named Mollicutes which characterized by its minute genome size and perpetually devoid of the cell wall. The aim of studies indicates the bacterial, molecular, immunopathological and immunohistochemical investigation in sheep with two experimental routs of infection in two parts. The current isolate of Mycoplasma ovipneumoniae was obtained from respiratory tract swabs of sheep in Basrah abattoir and then cultured in PPLO broth and agar and detected genetically by 16SrRNA and GOP3/MGSO. Nine sheep were divided into G1 and G2 groups inoculated with My. ovipneumoniae 5ml (1X107 CFU/ml) intranasal and intratracheal, G3 control group. IgGs levels on day 30 were high in tow groups. Fibrino-suppurative tracheitis and interstitial bronchopneumonia were prominent in gross appearance. Microscopically: necrosis of ciliated pseudostratified epithelium with inflammatory cells.  It could be concluded that My. ovipneumoniae was a primary causative agent of pleuro-bronchopneumonia in sheep.